Inflammatory gradient in Barrett's oesophagus: implications for disease complications. Issue 3 (1st September 2002) - Fitzgerald, R C; Abdalla, S; Onwuegbusi, B A; Sirieix, P; Saeed, I T; Burnham, W R; Farthing, M J G
Abstract : Introduction: Barrett's oesophageal epithelium (BE) is clinically important due to the associated inflammatory and malignant complications which are unevenly distributed throughout the BE segment. As the immunoregulatory environment may influence disease manifestations, we analysed the inflammatory and cytokine responses throughout the BE mucosa. We then investigated whether the inflammatory gradient is related to the distribution of metaplastic cell subtypes, epithelial exposure to the components of refluxate, or squamocolumnar cell interactions. Methods: Fifty consecutive patients with long segment BE were recruited. The segmental degree of endoscopic and histopathological inflammation was graded, and expression of interleukin (IL)-1β, IL-8, IL-4, and IL-10 were determined by ELISA following organ culture with or without addition of acid or bile salts. Mucin staining and IL-10 immunohistochemistry were performed. The effect of squamocolumnar interactions on cytokine expression were analysed using cocultures of squamous (OE-21) and BE (TE7) carcinoma cell lines. Results: There was a histopathological inflammatory gradient in BE. Inflammation was maximal at the new squamocolumnar junction with ≥2-fold increase in proinflammatory IL-8 and IL-1β expression. The proximal proinflammatory response could not be explained by the distribution of metaplastic subtypes. Pulsatile exposure of BE to acid and bile, as well as juxtaposition of BE to squamous epithelial cells in culture, increased expression of IL-1β. In contrast, inflammation was minimal distally with a significant increase in anti-inflammatory IL-10 expression and 4/6 cancers occurred distally. Conclusions: Specific cytokine responses may contribute to the localisation of inflammatory and malignant complications within BE.